2008
DOI: 10.1007/s10661-008-0326-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring human impacts on sandy shore ecosystems: a test of ghost crabs (Ocypode spp.) as biological indicators on an urban beach

Abstract: Sandy beaches comprise one of the most important coastal resources worldwide, providing habitats to threatened vertebrates, supporting underappreciated invertebrate biodiversity, and delivering crucial ecosystem services and economic benefits to mankind. Monitoring of the natural resource condition of sandy beaches and assessments of the ecological impacts of human disturbance are, however, rare on sandy shores. Because a crucial step in developing beach monitoring is to identify and test biological indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 29 publications
5
62
2
3
Order By: Relevance
“…Steiner & Leatherman (1981) suggested that ghost crabs become accustomed to increased levels of recreational use of a beach, and perform vertical migrations. However, even the positive effects of recreation such as food left by visitors can cause intense and continuous disturbance that may have negative impacts on the population of O. quadrata in the long term (Lucrezi et al 2009b). According to Turra et al (2005), it is believed that changes in beach morphodynamics alter the availability of food, influencing the size, distribution and abundance of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Steiner & Leatherman (1981) suggested that ghost crabs become accustomed to increased levels of recreational use of a beach, and perform vertical migrations. However, even the positive effects of recreation such as food left by visitors can cause intense and continuous disturbance that may have negative impacts on the population of O. quadrata in the long term (Lucrezi et al 2009b). According to Turra et al (2005), it is believed that changes in beach morphodynamics alter the availability of food, influencing the size, distribution and abundance of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Ghost crabs densities have been shown to be good biological indicators of human habitat disturbance on beaches. The crabs construct burrows in the sand matrix and densities can be easily estimated by counting the number of burrow openings on the sand surface (Barros 2001;Lucrezi et al 2008). A commonly observed response to disturbance caused by 4WDs is a decrease in crab densities in areas affected by cars, partly because vehicles can crush crabs inside and outside of their burrows (Moss and McPhee 2006;Schlacher et al 2007a).…”
Section: Field Surveysmentioning
confidence: 99%
“…The burrows of this species have circular or "hole" type openings and therefore counting the number of such burrow entrances is an effective tool to measure the population of Ocypode species on sandy shores (Moss and McPhee, 2006). As Ocypode crabs are form the highest trophic position amongst the invertebrate predators on sandy shores and also play an important role as prey for other vertebrate predators, so changes in the population of Ocypode crab can be used as a ecological indicator to predict the impact of various factors on sandy shore ecosystems (Chan et al, 2006;Valero-Pacheco et al, 2007;Lucrezi et al, 2009;Tureli et al, 2009). Ocypode ceratophthalmus is the most common brachyuran crab species occurring on the sandy shore habitat of Gujarat state (Trivedi and Vachhrajani, 2016) still ecology of local population of the species has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%